NOVÉ PŘÍSTUPY K PRÁCI S PŘÍKAZOVÝM ŘÁDKEM - LAVRINČÍK, Jan; Milan, KLEMENT; DANĚK, Jindřich (Trends in education, 2009)
MUELLER, J. P. Příkazový řádek Windows : pro Windows Vista, 2003, XP a 2000. 1. vyd. Brno : Computer Press, 2008. 656 s. ISBN 978-80-251-1961-7.